An all Prussian blue analog‐based aprotic sodium‐ion battery. Issue 2 (21st March 2022) - Xu, Li; Li, Hui; Du, Ting; Xue, Qing; Gao, Yuting; Yu, Zhuangzhuang; Bai, Huitao
Abstract: Sodium‐ion batteries have been regarded as ideal alternatives to lithium‐ion batteries in large‐scale electrochemical energy storage systems because of their low cost and abundant resources. However, the lack of high‐performance electrode materials with high energy density hinders the development of sodium‐ion batteries. Prussian blue analogs (PBAs) are especially regarded as superior cathodes for sodium‐ion batteries due to their high capacity and good electrochemical stability. The species and chemical environment of transition metal ions in PBAs greatly affect the electrochemical properties. In this study, we report a sodium cobalt hexacyanoferrate (Na x Co[Fe(CN)6 ]) and potassium iron hexacyanocobaltate (K x Fe[Co(CN)6 ]) nanoparticles through the coprecipitation method via changing the coordination structures of Co and Fe. With similar morphologies of well‐defined nanocubes and different M1 –CN–Mʹ2, the initial discharge capacities of Na x Co[Fe(CN)6 ] cathode and K x Fe[Co(CN)6 ] anode reach 104.1 and 354.8 mAh g −1, respectively. The sodium‐ion full cell assembled using Na x Co[Fe(CN)6 ] cathode and K x Fe[Co(CN)6 ] anode achieves a discharge capacity of 141.6 mAh g −1 . The outstanding performances of the Na x Co[Fe(CN)6 ] and K x Fe[Co(CN)6 ] are attributed to their stable structures, and the facile synthesis of Na x Co[Fe(CN)6 ] and K x Fe[Co(CN)6 ] makes them accessible for large‐scale applications. Abstract : Sodium‐ion full cell assembled using Na x Co[Fe(CN)6 ] cathode and K x Fe[Co(CN)6 ] anode achieves a discharge capacity of 141.6 mAh g −1 . The outstanding performances of Na x Co[Fe(CN)6 ] and K x Fe[Co(CN)6 ] are attributed to their stable structures, and the facile synthesis of Na x Co[Fe(CN)6 ] and K x Fe[Co(CN)6 ] makes them accessible for large‐scale applications.